PNM Mekar Syariah Sidoarjo Financing and Risk Management Community System - Umi Qurrotul Aini; Musthofa (al-Afkar, Journal For Islamic Studies, 2024)
The existence of PNM Mekaar aims to produce entrepreneurs or successful entrepreneurs from among women with limited capital to open a business or as capital to develop a business. Empowerment of this program is an effort by the government and includes state-owned enterprises whose priority is the welfare of the people, especially in financing loans, guarantees and training for women to manage finances with the help of PNM Mekkar. PNM Mekaar is a financial institution that has credit distribution where this is the main risk of bad credit, but in financing transactions PNM Mekaar Syariah Sidoarjo has the privilege of managing risk appropriately, so that there are not so many bad loans. Group financing community system with account officer guidance in grouping women's transactions for financing. The purpose of this research is to find out how the transaction system and risk management optimization are. This research uses a qualitative descriptive research method by obtaining data through interviews and observation.